2017
DOI: 10.18203/2394-6040.ijcmph20171321
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study to assess perception regarding mosquito borne diseases in urban areas of Belagavi city

Abstract: Background: Mosquito borne diseases are one of the major health problems in India. Due to growing population, unplanned urbanization, lack of awareness about the diseases and increasing number of slums in urban areas, the incidence of mosquito borne diseases is increasing simultaneously. To assess knowledge about mosquito borne disease and to impart awareness regarding prevention of mosquito borne diseases in the community. Methods: The present study was carried out in the urban field practice areas of departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Numerous publications show that a high living standard and educational level are related to more efficient management of potential larval habitats and reduced frequency of breeding sites in a neighborhood. Similar observations are found in endemic countries (50)(51)(52).…”
Section: Impact Of Socioeconomic Status On Mosquito Management Practicessupporting
confidence: 88%
“…Numerous publications show that a high living standard and educational level are related to more efficient management of potential larval habitats and reduced frequency of breeding sites in a neighborhood. Similar observations are found in endemic countries (50)(51)(52).…”
Section: Impact Of Socioeconomic Status On Mosquito Management Practicessupporting
confidence: 88%
“…This concept of a ‘clean’ yard may be attributed to the Department’s jingle on the radio which states ‘keep your surroundings clean, turn your buckets upside down, reduce dengue fever all around.’ Cleanliness is often a common theme found in studies surrounding knowledge of mosquito-borne diseases. A 2017 study from Belagavi city, India, Kularni et al [28]. found that 36.6% considered drainage and garbage as a common breeding place.…”
Section: Discussionmentioning
confidence: 99%
“…Now days, mosquito prevalence is increasing worldwide and has becomes a vector for spreading many harmful pathogenic diseases (Kulkarni and Biradar, 2017). For eradication of this ever increasing mosquito problem by synthetic pesticides will exhaust the environment.…”
Section: Introductionmentioning
confidence: 99%